A MATHEMATICAL-STATISTICAL EVALUATION OF CULTURAL TOURISM DEMAND AND OFFER - A CASE STUDY ON THE ATTRACTION OF THE MUSEUMS AND ITS ECONOMIC IMPACT IN BULGARIA - Delyana DIMOVA; Vanya GEORGIEVA; Nadezhda BLAGOEVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The current article presents a mathematical-statistical evaluation of cultural tourism demand in Bulgaria in terms of museum visits by region in the period 2013-2022. In parallel, the information related to the number of museums and exhibits is also examined. These indicated data are stored in a built relational database. The necessary information, for each of the six regions considered, is searched and extracted from it. Three sets of indicators are calculated and evaluated in connection with the subsequent processing of the studied elements. Hierarchical cluster analysis is also applied to the surveyed data. The results show that the pace of growth of the indicator (museum visits) in five of the mentioned regions is relatively fast in 2021-2022. The studied indicator decreases only in the North-West region during 2021, but there is an increase of about 24% in 2022. In the time interval 2016-2022, the number of museums does not change. The situation for this indicator in the period between 2018- 2022 is similar for the North Central region. The number of museums grows by about 26.67% and 12.50% for the South-East and South Central regions, respectively, in 2022. The largest number of exhibits is in five regions in 2022. Grouping the regions according to the number of museum visits presents two clusters. Grouping the regions according to the number of museums and exhibits leads to forming three and four clusters, respectively.